A Note on FC-Groups - Chernikov, N. S. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
Let G be an arbitrary FC-group, let R be its locally soluble radical, and let L/R = L(G/R). We prove that, for N ⊲ G, G/N is residually finite if R \(\subseteq\) N \(\subseteq\) L.